2011
DOI: 10.1039/c0cp02206c
|View full text |Cite
|
Sign up to set email alerts
|

Energy decomposition analysis based on a block-localized wavefunction and multistate density functional theory

Abstract: An interaction energy decomposition analysis method based on the block-localized wavefunction (BLW-ED) approach is described. The first main feature of the BLW-ED method is that it combines concepts of valence bond and molecular orbital theories such that the intermediate and physically intuitive electron-localized states are variationally optimized by self-consistent field calculations. Furthermore, the block-localization scheme can be used both in wave function theory and in density functional theory, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
309
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(322 citation statements)
references
References 217 publications
(358 reference statements)
9
309
2
2
Order By: Relevance
“…Such a reduction is of course accompanied by a concomitant increase in the total number of localised electrons, and becomes a powerful argument against the traditional role assigned to resonance in RAHBs, in agreement with previous experimental and theoretical studies which found no indication of an increased electron delocalisation in these types of H-bonds. [29][30][31][32][33][36][37][38][39][40] Since, as stated above, the interacting quantum atom partition provides a unique combination of electron and energy descriptors, we may now explore the energy features of the formation of the HB associated with the previously discussed changes in R(r) and R 2 (r 1 ,r 2 ). Following the previous line of reasoning, we first examine the energetics of resonance and bond order equalization, which are indicated in terms of the covalent, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Such a reduction is of course accompanied by a concomitant increase in the total number of localised electrons, and becomes a powerful argument against the traditional role assigned to resonance in RAHBs, in agreement with previous experimental and theoretical studies which found no indication of an increased electron delocalisation in these types of H-bonds. [29][30][31][32][33][36][37][38][39][40] Since, as stated above, the interacting quantum atom partition provides a unique combination of electron and energy descriptors, we may now explore the energy features of the formation of the HB associated with the previously discussed changes in R(r) and R 2 (r 1 ,r 2 ). Following the previous line of reasoning, we first examine the energetics of resonance and bond order equalization, which are indicated in terms of the covalent, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The ALMO EDA is a descendent of the Kitaura-Morokuma EDA [400] (which is perhaps the first EDA method), and uses the same definition of the frozen interactions. It is also closely related to the block-localised wave function EDA [401,402] because both approaches use the same variational definition of the polarisation energy that is an upper limit to the true extent of polarisation [403]. A distinctive advantage of the ALMO-EDA is that the charge-transfer contribution is separated into pairwise additive contributions associated with forward and back-donation, and a non-pairwise decomposable higher order contribution, which is very small for typical intermolecular interactions.…”
Section: Energy Decomposition Analysismentioning
confidence: 99%
“…69,70 Moreover, they treat both inter-and intramolecular 18,19,43,71 (including through-bond) interactions on equal footing (including through bond) and, thus, capably describe phenomena that are of a mixed or non-covalent nature, e.g., dative bonds, 27,72,73 as well as chemisorption and physisorption processes 221,222 (through a "periodic EDA" by Tonner et al 223 ). Owing to the numerous levels of accuracy possible, including multireference variants, 41,74 it is also possible to treat strongly correlated systems 75 and molecules having elongated bonds. Owing to an unambiguous definition of CT, EDAs are often used to identify and quantify charge transfer interactions, 22,27,48,76 frequently in conjunction with ALMO-CTA, 77,78 which is complementary to ALMO-EDA.…”
Section: Figmentioning
confidence: 99%